2020
DOI: 10.3390/en13061498
|View full text |Cite
|
Sign up to set email alerts
|

Transient Flow of a Horizontal Well with Multiple Fracture Wings in Coalbed Methane Reservoirs

Abstract: Horizontal wells with multi-stage fractures have been widely used to improve coalbed methane (CBM) production from coalbed methane reservoirs. The main focus of this work is to establish a new semi-analytical method in the Laplace domain and investigate the transient pressure behavior in coalbed methane reservoirs. With the new semi-analytical method, flow regimes of a multi-fractured horizontal well in coalbed methane reservoirs were identified. In addition, the sensitivities of fracture conductivity, diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To obtain the associated constants D 1 , D 2 , D 3 , note that, when replacing the solutions obtained, the Equations (48)-(50) in the boundary conditions, Equations (25) and (26), the following matrix system is reached…”
Section: General Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the associated constants D 1 , D 2 , D 3 , note that, when replacing the solutions obtained, the Equations (48)-(50) in the boundary conditions, Equations (25) and (26), the following matrix system is reached…”
Section: General Solutionmentioning
confidence: 99%
“…On the other hand, Tian et al [25] investigated the transient pressure behavior in a horizontal well in coalbed methane reservoirs with multiple fracture wings by identifying the characteristic flow periods. Meanwhile, Gao et al [26] addressed the problem of fast pressure drop and gas well abandonment caused by well interference; divided the region around the MFHW into three regions and solved the model using finite volumes and concluded that the IWCM can effectively control the resources within the reservoir around the well.…”
Section: Introductionmentioning
confidence: 99%
“…The RTA of a multi-staged hydraulically fractured horizontal well is complicated and may require additional information, such as a micro-seismic interpretation, to obtain promising results [1,2,12,13]. The production history (recorded on a daily basis) of a typical horizontal well may exhibit five flow regimes, namely, early radial, formation linear, elliptical, pseudo-radial, and boundary-dominated flow regimes [1].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of coal seam pressure difference on single well production is demonstrated. Tian et al [23] studied the flow characteristics of horizontal well with multiple fracture wings. The semianalytical solution model of horizontal well with multiple fracture wings is established, and the flow stage of the model is defined.…”
Section: Introductionmentioning
confidence: 99%